Perception of Nervous System Physiology in “Theory of Organic Beings” by Jędrzej Śniadecki (1768–1838) - Matulaitytė, Gražina; Sakalauskaitė-Juodeikienė, Eglė (Neurologijos seminarai, 2024)
Jędrzej Śniadecki (1768–1838) was a graduate of the universities of Krakow and Pavia, a professor of chemistry at Vilnius University, a prominent Vilnius physician, one of the founders of the Vilnius Medical Society, and the editor of the scientific and cultural journal Dziennik Wileński. He was also the author of many publications, including the three-volume treatise Teorya jestestw organicznych (“Theory of Organic Beings”, I–III volumes were published in 1838). According to modern science historians, this opus magnum was one of the first and most important monographs exploring the fields of biochemistry and physiology in the Western world at the time. In this article, we examine how Jędrzej Śniadecki introduced the basics of the anatomy and physiology of the nervous system, how he explained the principles of nerve functions, the process of sleep and its significance to human health. Also, by comparing Śniadecki’s postulates with the 17th–19th-century publications of the Western European scientists, we discuss whether Jędrzej Śniadecki was a scientist of his time – a disseminator of the most advanced medical theories and scientific knowledge, or he was actually an original researcher in the field of nervous system physiology, an innovator who was ahead of his time.